Identifikasi Tingkat Kerentanan Bencana Kota Sukabumi - Adinata Wirasena; Jauharah Nur Khalishah; Qori Nabilla; Shabina Nurul Zakiyyah; Muzani Jalaluddin (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
The city of Sukabumi is an urban area that has a high level of vulnerability to various disasters, especially hydrometeorological disasters such as floods and landslides, which are influenced by high rainfall, topography, and land use. This study analyzes the level of disaster vulnerability in the city of Sukabumi through the integration of social, economic, physical, and environmental aspects using a quantitative SIG-based spatial approach. This region has a high risk of hydrometeorological disasters due to intense rainfall, hilly topography, and changes in land use. Official data from BPS and BIG were processed through normalization, weighting, and mapping to produce a composite index per subdistrict. The results of the study show that 86% of subdistricts are in the moderate vulnerability category, namely Gunung Puyuh (0.41), Cikole (0.49), Citamiang (0.36), Warudoyong (0.503), Baros (0.356), and Cibeureum (0.449). Only 14% of subdistricts are in the low category, namely Lembursitu (0.321). The subdistrict with the highest vulnerability level is Warudoyong (0.503), while the lowest is Lembursitu (0.321). These findings emphasize the need for integrated mitigation strategies, especially in areas with moderate vulnerability indices that dominate the entire city.